PERAN GURU DALAM INTERNALISASI KARAKTER PEDULI SOSIAL MELALUI KEGIATAN PALANG MERAH REMAJA DI SMP N 7 SURAKARTA TAHUN 2025 - Aliffi Tarisa Pramesti; Anita Trisiana; Siti Supeni (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe the implementation, analyze the forms of activities, and examine the role of Civics (PPKn) teachers in internalizing social care values through Youth Red Cross activities at SMP N 7 Surakarta in 2025. The research employed a descriptive qualitative approach involving the principal, vice principals, Youth Red Cross advisor, Civics teachers, and students as research subjects. Data were collected through observation, interviews, and documentation, and validated using source and method triangulation. The data were analyzed through the stages of data collection, data reduction, data display, and conclusion drawing. The findings indicate that Youth Red Cross activities enhance students’ knowledge, skills, and attitudes of social care, reflecting civic responsibility and civic virtue. The activities include in-school programs such as the Tri Bhakti experience and out-of-school activities such as donations, evacuation training, social services, and first aid treatment for minor injuries. Furthermore, Civics teachers play roles as educators, instructors, and mentors in fostering students’ social care character, ensuring that the internalization of these values is carried out in a structured and sustainable manner.